2016
DOI: 10.4236/ojms.2016.61007
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Wind Power for Marine Conservation

Abstract: The seas of northern Europe are strongly affected by human activities and there is a great need for improved marine conservation. The same region is also the current hotspot for offshore wind power development. Wind farms can have negative environmental impacts during construction, but during the operational phase many organisms are attracted to the foundations and thereby may also find refuge from fisheries. Given the recent implementation of marine spatial planning in Europe and elsewhere, this is a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 56 publications
0
24
0
2
Order By: Relevance
“…). The ability to find the source and destination of young fish and the level of spatial structuring of populations is critical for the management of marine protected areas (Planes et al ; Berglund et al ), coastal development (Cicin‐Sain and Belfiore ), offshore wind farms (Hammar et al ), and fisheries (Fogarty et al ). For example, in the northeast of UK, the local turbot population collapsed in 1970s due to overfishing.…”
Section: Discussionmentioning
confidence: 99%
“…). The ability to find the source and destination of young fish and the level of spatial structuring of populations is critical for the management of marine protected areas (Planes et al ; Berglund et al ), coastal development (Cicin‐Sain and Belfiore ), offshore wind farms (Hammar et al ), and fisheries (Fogarty et al ). For example, in the northeast of UK, the local turbot population collapsed in 1970s due to overfishing.…”
Section: Discussionmentioning
confidence: 99%
“…Gradual increasing was then observed, and in 2012 the population inside Nysted offshore farm reached 29% of the baseline level. It should be stressed, however, that the decrease of porpoise habituation was not observed in Rødland II based, similarly to the Nysted farm, on gravity foundations and, as a consequence, there was no pile driving during placement (Hammar et al 2016). Furthermore, some monitoring results from another offshore wind farms in the Baltic and North Sea showed that porpoise inhabitation returned to normal levels after the construction works (see (Hammar et al 2016) and references given there) or even increased in comparison with the level before placement (Scheidat et al 2011).…”
Section: Wind Powermentioning
confidence: 89%
“…by the cessation of fishing activity and the creation of artificial reefs. Furthermore, OWFs can even serve as refuges for marine fauna and flora that are nearly as effective as existing marine protected areas (Hammar et al, 2016). However, reliable international assessment -especially concerning the cumulative impacts of OWFs over a longer period -remains challenging.…”
Section: Summary and Outlook: Lessons Learned From 10 Years Of Offshomentioning
confidence: 99%
“…Regarding the impacts of OWFs on benthos (fauna living in, on or nearby the seabed), an increase in their number was observed after OWF construction (Ashley et al, 2014;Coates et al, 2014;Dannheim et al, 2014;Vaissière et al, 2014;Bergman et al, 2015;Schuster et al, 2015;Hammar et al, 2016). However, the species composition changed as a result of the new habitats.…”
mentioning
confidence: 99%
See 1 more Smart Citation